2021
DOI: 10.1371/journal.pone.0249958
|View full text |Cite
|
Sign up to set email alerts
|

The effect of disagreement on children’s source memory performance

Abstract: Source representations play a role both in the formation of individual beliefs as well as in the social transmission of such beliefs. Both of these functions suggest that source information should be particularly useful in the context of interpersonal disagreement. Three experiments with an identical design (one original study and two replications) with 3- to 4-year-old-children (N = 100) assessed whether children’s source memory performance would improve in the face of disagreement and whether such an effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…This is important in many different types of social situations, from handling disagreements to managing social obligations (Mahr & Csibra, 2018). Relatedly, empirical investigations have targeted the question whether situations in which children anticipate that their beliefs would need to be justified-such as disagreements-prompts them to more accurately recall and scrutinize the source of their knowledge (Mahr et al, 2021). Evidence shows that the source memory performance-identifying whether they know the content of a drawer because they saw it or have been told about it (based on the experimental design of Gopnik & Graf, 1988)-of 4 year old children is better in situations involving disagreement expressed by another person.…”
Section: Epistemic Vigilancementioning
confidence: 99%
“…This is important in many different types of social situations, from handling disagreements to managing social obligations (Mahr & Csibra, 2018). Relatedly, empirical investigations have targeted the question whether situations in which children anticipate that their beliefs would need to be justified-such as disagreements-prompts them to more accurately recall and scrutinize the source of their knowledge (Mahr et al, 2021). Evidence shows that the source memory performance-identifying whether they know the content of a drawer because they saw it or have been told about it (based on the experimental design of Gopnik & Graf, 1988)-of 4 year old children is better in situations involving disagreement expressed by another person.…”
Section: Epistemic Vigilancementioning
confidence: 99%
“…While the correct conceptual analysis of “memory” is debated in philosophy (e.g., Michaelian & Robins, 2018), hardly anyone denies that we have different concepts for memory and imagination. Finally, claims to remembering and imagining have starkly different social consequences and are applied in different contexts (Mahr & Csibra, 2020; 2021; Mahr, Mascaro, Mercier, & Csibra, 2021). In sum, remembering and imagining seem to be distinguished as a matter of phenomenology, as a matter of concepts, and as a matter of social practice.…”
Section: Mnemicity As Cognitive Attributionmentioning
confidence: 99%
“…In Mahr et al. (2021), we allowed 3‐5 year‐old children to find out about the contents of a container either by looking inside it themselves or by being told about it by the experimenter. Next, children were faced with an interlocutor who asked them what the contents of the container were and then either agreed or disagreed with their answer before asking them about the source of their belief (“How do you know that…?”).…”
Section: Individual Aspects Of Mnemicity Attributionmentioning
confidence: 99%
“…Since very little empirical work has directly assessed children's understanding of epistemic accountability, an important direction for future research is to investigate how children understand the responsibilities embedded in beliefs acquired under conditions of epistemic collaboration. Although some recent work has shown that child listeners can hold speakers accountable by selectively rewarding (Li, & Koenig, 2020; Ronfard et al., 2019) and informing (Dunfield, Kuhlmeier, & Murphy, 2013) more reliable speakers over unreliable speakers, and may have better source memory when their newly acquired beliefs were challenged (Mahr, Mascaro, Mercier, & Csibra, 2021), none of this work has examined children's judgments of the responsibilities shared between the speaker and listener in interpersonal or collaborative transactions. Thus, one line of interesting research could directly investigate epistemic buck passing by prompting children to acquire new beliefs, or update old beliefs through an interpersonal, collaborative route (i.e., a speaker making a commitment to the child listener about the truth of the belief), and expect to find different patterns of responses when children's beliefs are challenged.…”
Section: Interpersonal Commitments In Testimonial Transactionsmentioning
confidence: 99%